PERENCANAAN PRODUKTIVITAS KERJA DARI HASIL EVALUASI PRODUKTIVITAS DENGAN METODE FISHBONE DI PERUSAHAAN PERCETAKAN KEMASAN PT.X - Murnawan, Heri (Heuristic, 2014)
Productivity is an important factor that affects the progress and setbacks of a company.Evaluation and planning is indispensable productivity after making measurements and it will bethe foundation to move on to the next cycle of the productivity improvements in the future. Amethod that can be used in the evaluation is a method Fishbone Diagram and continue planningwith Objective Matrix in accordance with the results of previous measurements. In the evaluationand planning, the selection of primary and secondary causes is an important step, because theselection can be used to determine the cause of the decline in productivity in the measurementperiod, the planning for the next period , and improved productivity for the company. The studytook place in Packaging Printing Company PT " X " , Rungkut Industry , Surabaya in January -June 2013.The purpose of this follow-up study is to evaluate and analyze productivity by using a FishboneDiagram productivity and plan for the next period in accordance with the method of measuringthe PT " X " . The research was conducted on the following five criteria: the target production,raw materials, energy, labor and machine hours . Evaluation and planning is done to determinethe decrease in productivity as well as during the planning period January 2013 - July 2013.The results showed the indicators of productivity that have the most dominant influence on theachievement levels of labor productivity in the enterprise is the criteria of productivity GoodProduct Quantity / Quantity Production Target , Good Product Quantity / Use of Raw Materials ,Good Product Quantity / Quantity Energy Use . Because the productivity of each of these criteriahave a large enough weight that is above 19 %. Changes in the level of achievement ofperformance criteria in all three partial indicators of productivity are always followed bysignificant changes in the achievement of performance indicators in total.Kata kunci: Perencanaan Produktivitas Kerja, Diagram Fishbone, Industri Kemasan